2019
DOI: 10.1055/s-0039-1692185
|View full text |Cite
|
Sign up to set email alerts
|

Physician Burnout among Members of the Society for Maternal-Fetal Medicine

Abstract: Objective To determine the rate of physician burnout among maternal-fetal medicine subspecialists and identify associated factors. Study Design Noninternational members of the Society for Maternal-Fetal Medicine (SMFM) were surveyed regarding burnout using a validated tool specifically designed for health professionals (Maslach Burnout Inventory—Human Services Survey). Burnout was defined as exceeding established cutoffs for emotional exhaustion or depersonalization. Demographic information and pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Internal factors represent all aspects of an individual, such as gender, age, skills, personality, and perceptions. Many studies have found that female physicians report more mental health issues such as burnout than do male physicians [ 3 , 17 , 23 26 ] with work-home conflict proposed as a possible reason for this gender difference [ 3 , 24 , 27 ]. However, some studies have found no significant difference in burnout between male and female physicians [ 2 , 5 , 11 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internal factors represent all aspects of an individual, such as gender, age, skills, personality, and perceptions. Many studies have found that female physicians report more mental health issues such as burnout than do male physicians [ 3 , 17 , 23 26 ] with work-home conflict proposed as a possible reason for this gender difference [ 3 , 24 , 27 ]. However, some studies have found no significant difference in burnout between male and female physicians [ 2 , 5 , 11 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of autonomy at work has been found to correspond with higher physician burnout in multiple studies [ 3 , 4 , 27 , 29 ]. Physicians with greater authority or leadership positions have been found to report lower burnout and greater fulfillment [ 23 , 32 ], with academic physicians who experienced conflicts with hospital leaders also reporting higher burnout [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, perceived lack of support in work life and at home were strongly associated with burnout [22 p683]. The aim of another study was to identify the prevalence of burnout syndrome among physicians of maternal-fetal medicine (n=538) and its associated factors in the United States [23]. The prevalence of burnout syndrome among respondents was 56,5%, whereas 45,4% of participants faced high levels of EE, 31,4% experienced high levels of DP, and 11% had low PA (MBI-HSS) [23].…”
Section: North and South Americamentioning
confidence: 99%
“…The aim of another study was to identify the prevalence of burnout syndrome among physicians of maternal-fetal medicine (n=538) and its associated factors in the United States [23]. The prevalence of burnout syndrome among respondents was 56,5%, whereas 45,4% of participants faced high levels of EE, 31,4% experienced high levels of DP, and 11% had low PA (MBI-HSS) [23]. Less career satisfaction, dissatisfaction with supervisor, after-work charting, self-perception burnout, and fewer years in practice were positively associated with burnout syndrome [23].…”
Section: North and South Americamentioning
confidence: 99%
“…17 To accomplish this, it is inevitable to regulate and manage working hours of physicians. The overload of working in MFM doctors could increase the rate of burnout more than the doctors in other subspeciality areas, 18 also more than those in Gynecologic Oncology in terms of the subspeciality in OB/GYN. 19 Therefore, working long hours cannot be sustainable for not only the MFM provision system but also individuals of OB/GYN doctors.…”
Section: Figurementioning
confidence: 99%